(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aims at investigating the antibacterial potential of ethanolic extract of Camellia sinensis (common name: Green tea) and Azadirachta indica (common name: Neem) leaves on methicillin-resistant Staphylococcus aureus (MRSA) and shiga-toxigenic Escherichia coli (STEC). Materials and Methods: Fresh leaves were processed and extracted by 99% ethanol and reconstituted with 50% ethanol before testing. Disk diffusion and broth microdilution methods were used to determine zone diameter of inhibition (ZDI) and minimum inhibitory concentration (MIC), respectively. Nutrient agar plate was used to estimate the minimum bactericidal concentration (MBC). Results: Maximum ZDI value was observed for green tea against MRSA (7.5 mm) and minimum for neem (4.9 mm). Moreover, the highest ZDI against STEC was also for green tea and the combination of green tea and neem (4.5 mm). The MIC values of green tea extract were 15.625 and 31.25 mg/ml against MRSA and STEC, respectively, whereas the MIC of neem was 31.25 and 125 mg/ml, respectively. The combination had similar MIC (46.87 mg/ml) against both organisms. Green tea showed the lowest MBC values, 31.25 and 62.5 mg/ml, against MRSA and STEC, respectively. However, MBC of neem and the combination against MRSA and STEC were found >250 mg/ml, >500 mg/ml and 93.75 mg/ml, >375 mg/ml, respectively. Conclusion: Green tea and neem leaves showed good antimicrobial effects and can be used to explore novel antimicrobial compounds against MRSA and STEC. J. Adv. Vet. Anim. Res., 6(2): 247-252, June 2019